Prevalence and early‐life risk factors of school‐age allergic multimorbidity: The EuroPrevall‐iFAAM birth cohort. Issue 9 (8th June 2021) - Sigurdardottir, Sigurveig T.; Jonasson, Kristjan; Clausen, Michael; Lilja Bjornsdottir, Kristin; Sigurdardottir, Sigridur Erla; Roberts, Graham; Grimshaw, Kate; Papadopoulos, Nikolaos G.; Xepapadaki, Paraskevi; Fiandor, Ana; Quirce, Santiago; Sprikkelman, Aline B.; et al.
Abstract: Background: Coexistence of childhood asthma, eczema and allergic rhinitis is higher than can be expected by chance, suggesting a common mechanism. Data on allergic multimorbidity from a pan‐European, population‐based birth cohort study have been lacking. This study compares the prevalence and early‐life risk factors of these diseases in European primary school children. Methods: In the prospective multicentre observational EuroPrevall‐iFAAM birth cohort study, we used standardized questionnaires on sociodemographics, medical history, parental allergies and lifestyle, and environmental exposures at birth, 12 and 24 months. At primary school age, parents answered ISAAC‐based questions on current asthma, rhinitis and eczema. Allergic multimorbidity was defined as the coexistence of at least two of these. Results: From 10, 563 children recruited at birth in 8 study centres, we included data from 5, 572 children (mean age 8.2 years; 51.8% boys). Prevalence estimates were as follows: asthma, 8.1%; allergic rhinitis, 13.3%; and eczema, 12.0%. Allergic multimorbidity was seen in 7.0% of the whole cohort, ranging from 1.2% (Athens, Greece) to 10.9% (Madrid, Spain). Risk factors for allergic multimorbidity, identified with AICc, included family‐allergy‐score, odds ratio (OR) 1.50 (95% CI 1.32–1.70) per standard deviation; early‐life allergy symptoms, OR 2.72 (2.34–3.16) for each symptom; and caesarean birth, OR 1.35 (1.04–1.76). Female gender, OR 0.72 (0.58–0.90); older siblings, OR 0.79 (0.63–0.99); and day care, OR 0.81 (0.63–1.06) were protective factors. Conclusion: Allergic multimorbidity should be regarded as an important chronic childhood disease in Europe. Some of the associated early‐life factors are modifiable and may be considered for prevention strategies. Abstract : Allergic multimorbidity (coexistence of asthma, eczema and allergic rhinitis) is common among European children at primary school age, with 7% of study participants affected. Protective factors identified in the study include female sex, having older siblings and attending day care. Risk factors include history of allergic diseases in first‐degree family members, early‐age symptoms and caesarean birth.